Cross shift changes in lung function among bar and restaurant workers before and after implementation of a smoking ban. Issue 7 (21st March 2006) - Skogstad, M; Kjærheim, K; Fladseth, G; Gjølstad, M; Daae, H L; Olsen, R; Molander, P; Ellingsen, D G
Abstract : Objective: To study possible cross shift effects of environmental tobacco smoke (ETS) on pulmonary function among bar and restaurant employees before and after the implementation of a smoking ban in Norway. Methods: The study included 93 subjects employed in 13 different establishments in Oslo. They were examined at the beginning and end of a workshift both while ETS exposure was present and when smoking was banned. The mean exposure level of nicotine and total dust before the ban was 28 μg/m 3 (range 3–65) and 275 μg/m 3 (range 81–506), respectively. Following the smoking ban, the mean level of nicotine and total dust was 0.6 μg/m 3 and 77 μg/m 3, respectively. Assessment of lung function included dynamic lung volumes and flows. Results: The cross shift reduction in forced vital capacity (FVC) among 69 subjects participating in both examinations changed from 81 ml (SD 136) during exposure to ETS to 52 ml (SD 156) (p = 0.24) following the smoking ban. The reduction in forced expired volume in one second (FEV1) during a workshift, was borderline significantly reduced when comparing the situation before and after the intervention, by 89 ml (SD = 132) compared to 46 ml (SD = 152) (p = 0.09), respectively. The reduction in forced mid-expiratory flow rate (FEF25–75% ) changed significantly from 199 ml/s (SD = 372) to 64 ml/s (SD = 307) (p = 0.01). Among 26 non-smokers and 11 asthmatics, the reduction in FEV1 and FEF25–75% was significantly larger during ETS exposure compared to after the smoking ban. There was an association between the dust concentration and decrease in FEF25–75% before the ban among non-smokers (p = 0.048). Conclusions: This first study of cross shift changes before and after the implementation of a smoking ban in restaurants and bars shows a larger cross shift decrease in lung function before compared with after the implementation of the ban.